Facilitating Productive Struggle in an Online Secondary Education Mathematics Methods Course: Experiences of Pre-Service Teachers - Casler-Failing, Shelli L. (Journal of Teaching and Learning, 2024)
This research investigated preservice teachers’ (PSTs) experiences with productive struggle in an online environment, and how it influenced their pedagogical knowledge. This action research study reports on secondary mathematics pre-service teachers (PSTs) who completed mathematical tasks in weekly synchronous Zoom sessions to develop their understanding of productive struggle. Vygotsky’s (1978) Social Constructivist Theory and the growth mindset framework (Boaler, 2016; Dweck 2006; 2008) provided the lenses through which the research was designed and analyzed. Findings show that presenting opportunities for PSTs to experience productive struggle informs their pedagogical practice, and that providing this experience in an online environment is possible. PSTs gained an increased understanding of the importance of collaborative work, asking purposeful questions, and the alignment between productive struggle and improved mathematical understanding.